2020
DOI: 10.33024/hjk.v13i4.1670
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh posisi condong kedepan dan terapi pursed lips breathing terhadap derajat sesak napas penderita Penyakit Paru Obstruktif Kronik (PPOK)

Abstract: Pursed lips breathing and an forward leaning posture to reduce dyspnea in Chronic Obstructive Pulmonary Disease (COPD) patients.Background: An in-depth personal interview in December 2019 with nurses of Dr. H. Abdul Moeloek Hospital of Lampung Province where the hospital is one of the referred hospitals for COPD in Lampung Province found that the COPD patient number increased every day. In average, there were 20 COPD patients registered every day with mostly having complaint of heavy breathless and recurring o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…Our study demonstrated that most of the COPD patients were heavy smokers, which are similar to results reported by other researchers in Adam Malik General Hospital (Medan) and M. Djamil Hospital (Padang), Indonesia [14], [15]. Most of the patients had Stage III COPD, and these patients had deteriorated clinically and were being treated in intensive care in the hospital.…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrated that most of the COPD patients were heavy smokers, which are similar to results reported by other researchers in Adam Malik General Hospital (Medan) and M. Djamil Hospital (Padang), Indonesia [14], [15]. Most of the patients had Stage III COPD, and these patients had deteriorated clinically and were being treated in intensive care in the hospital.…”
Section: Discussionsupporting
confidence: 89%
“…Namely, expiration is more extended than inspiration to facilitate the expulsion of carbon dioxide from the body that is held back due to airway obstruction. Play therapy blowing superbubbles is intended for children who have problems with the respiratory system, especially asthma, with the aim that lung function in children will increase and become normal (Isnainy & Tias, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Sesak nafas pada pasien PPOK diakibatkan karena peningkatan produksi sputum yang pada akhirnya menutupi jalan nafas. Sehingga terapi yang dirasa efektif adalah terapi yang berakibat terbuangnya sputum (Isnainy and Tias, 2020).…”
Section: ) Efektifitas Kombinasi Terapi Batuk Efektif Dan Pursed Lipunclassified